Why is it problematic for technicians to say they teach in higher education? - Tim Savage; Kelly Vere (Journal of Learning Development in Higher Education)
This article challenges the popular misconception that technicians do not teach within higher education (HE). Writing from their experiences as technicians and educational researchers within the creative arts (Savage) and Science, Technology, Engineering and Maths (STEM) (Vere), the authors question why many technicians feel unable to describe their teaching activities as teaching, calling for greater recognition of technicians’ pedagogic contribution to the sector, while also arguing that through the activities of teaching, the boundaries between academic and technical roles have become increasingly blurred.